Cobalt‐Catalyzed Electrophilic Cyanation of Arylzinc Halides with N‐Cyano‐N‐phenyl‐p‐methylbenzenesulfonamide (NCTS). Issue 16 (13th August 2015) - Cai, Yingxiao; Qian, Xin; Rérat, Alice; Auffrant, Audrey; Gosmini, Corinne
Abstract: The cobalt‐catalyzed cross‐coupling of organozinc bromides with N ‐cyano‐ N ‐phenyl‐ p ‐methylbenzenesulfonamide (NCTS) is described. The same cobalt catalyst, cobalt(II) bromide, was used for both the synthesis of the organozinc species and the cross‐coupling reaction. However in this case, a catalytic amount of zinc dust is necessary in the second step to release the low‐valent cobalt. Under these mild conditions, moderate to excellent yields of different benzonitriles were obtained. Abstract :